Guidelines of the Polish Society of Ophthalmology for the treatment of exudative age-related macular degeneration - Misiuk-Hojło, Marta; Grabska-Liberek, Iwona; Michalska-Małecka, Katarzyna; Mrukwa-Kominek, Ewa; Romanowska-Dixon, Bożena; Stopa, Marcin; Szaflik, Jacek; Szaflik, Jerzy; Ulińska, Magdalena; E. Adamiec-Mroczek, Joanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2021)
Age-related macular degeneration (AMD) is the most common cause of severe visual impairment in older adults in the developed world. Especially neovascular AMD, characterized by rapid progression and a significant reduction in visual acuity, until recently was a therapeutic challenge. The last 15 years have been a period of development of new diagnostic and treatment possibilities. The paper presents recommendations of the Polish Ophthalmological Society for the management of neovascular age-related macular degeneration based on the latest publications.